Embedding Character Education through Transformational Leadership: A Qualitative Study of Principal-Led Human Resource Development in an Indonesian Muhammadiyah Primary School Context - Andi Prasetiyo; Sutama; Fitri Puji Rahmawati; Siti Marpuah (Universitas Muhammadiyah Surakarta, 2025)
This study investigates the transformational leadership practices of elementary school principals in the context of human resource management, an area often overlooked compared to organizational or corporate settings. Conducted at an Indonesian Muhammadiyah Elementary School. This ethnographic qualitative research explores the cultural dynamics and leadership behaviors influencing the management of school personnel. Participants included the principal, curriculum coordinator, facilities staff, treasurer, teachers across grades I–VI, school employees, and grade VI students. Data were gathered through observation, interviews, and document analysis, and analyzed via data reduction, data display, and conclusion drawing. The findings reveal that the principal exhibits a blend of democratic, visionary, and semi-authoritarian leadership styles. Notably, transformational leadership was enacted through inspirational motivation and idealized influence, demonstrated via multimedia, storytelling, and structured spiritual routines. The principal communicated the school’s vision and mission clearly, serving as a role model while initiating various human resource development initiatives—such as refining standard operating procedures (SOPs), enhancing teacher and staff competencies, improving academic performance, and expanding professional networks. The study underscores that the principal’s effective transformational leadership significantly contributes to elevating teacher motivation, enthusiasm, achievement, and performance, ultimately enhancing the overall educational quality at the school.